Theme And Idea In Isajan Sultan's Story "Wooden Shoes" (“Yog`Och Kovush”) - Ibragimova Dildora Inomjonovna (Zien Journals, 2024)
The article examines the main and auxiliary themes of Isajon Sultan's story “Wooden shoes” ("Yog`och Kovush"), the main idea of the work. The importance of the work in modern storytelling is noted
Keywords: Isajon Sultan; story; Wooden shoes